Histoire de constructions et reconstruction de l’Histoire : l’écriture documentaire de Patrick Keiller - Isabelle Cases (Revue LISA)
Patrick Keiller, who was trained as an architect, is well known for documentaries which mix past and present facts with fiction, often through a succession of still shots showing monuments, buildings or sites presented by an unconventional narration. By doing so, he intends to underline the failure of British housing, architectural and environmental policies, while analyzing the harmful consequences of capitalism on the country. Patrick Keiller follows a tradition in the British documentary which explored these issues at various times to refer to slum clearances, the war effort, the construction of New Towns or, more recently, the birth of a heritage industry and its consequences. He offers a vision of the History of his country through its architecture and landscape and associates his images with very numerous references to events, thinkers, artists or works of art, without any strict chronology, as he follows his main character in his reflections and travels. He thus re-writes History in both a poetic and deeply committed way.